2017
DOI: 10.1080/14992027.2017.1313461
|View full text |Cite
|
Sign up to set email alerts
|

Electric field-navigated transcranial magnetic stimulation for chronic tinnitus: a randomized, placebo-controlled study

Abstract: Despite the significant effects of rTMS on tinnitus, differences between active and placebo groups remained non-significant, due to large placebo-effect and wide inter-individual variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 43 publications
2
52
0
1
Order By: Relevance
“…Twenty-six articles remained when we removed the duplicates and screened the titles and abstracts. After screening the full text, we included 10 RCTs [12,[14][15][16][17][18][19][20][21][22] with a total of 567 participants in our meta-analysis ( Figure 1). Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-six articles remained when we removed the duplicates and screened the titles and abstracts. After screening the full text, we included 10 RCTs [12,[14][15][16][17][18][19][20][21][22] with a total of 567 participants in our meta-analysis ( Figure 1). Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of bias of the nine included studies is summarized in Figure 2. Seven studies [12,14,[16][17][18][19]21] described the method of random sequence generation in detail, while three studies [15,20,22] did not provide sufficient information about randomized methods. Five studies [12,14,16,17,21] reported adequate allocation concealment.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Six stimulation positions for rTMS were localized in reference to Sahlsten et al (3). Stimulation positions consisted of anterior (aSTG), middle (mSTG), and posterior (pSTG) parts of the left and right STG.…”
Section: Rtms Test Sessionmentioning
confidence: 99%
“…Fifteen studies [5,15,17,19,20,23,27,[27][28][29][30][31]36,39] reporting adverse events after rTMS sessions were meta-analysed using a xed effects model, with nonsigni cant heterogeneity among the studies (I 2 = 37%, P = 0.13). The results showed a nonsigni cant difference in the incidence of adverse events between the rTMS and sham-rTMS groups (12.55% vs. 13.38%; OR: 1.11, 95% CI: 0.51-2.42; P = 0.79) ( Fig.…”
Section: Adverse Eventsmentioning
confidence: 99%